CURRENT CONDITION, INDICATIONS AND CONTRAINDICATIONS OF CONSERVATIVE METHODS OF TREATMENT OF FRACTURES OF THE LOWER JAW - Steblovskyi, D.V.; Avetikov, D.S.; Svyryda, O.S.; Lychman, V.O.; Lokes, K.P.; Toropov, O.A. (World of Medicine and Biology, 2025)
This review explores the conservative approaches to treating mandibular fractures, focusing on methods like intermaxillary ligatures, splints, and orthopedic devices. It details the fabrication and application of common splints, such as the Tigerstedt splint, and describes various types of intermaxillary fixation. The role of medication, including analgesics, antibiotics, and supplements, is discussed. The article also outlines indications for conservative treatment, including linear fractures without significant displacement, high-risk patients, and pediatric cases. Furthermore, it addresses potential disadvantages such as muscle atrophy, joint contractures, and occlusal dysfunction. The text also covers strategies for preventing complications in surgical treatment, emphasizing multidisciplinary approaches and evidence-based practices to improve patient outcomes.